1993
DOI: 10.1029/93jc02298
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal restratification and turbulence in the oceanic surface mixed layer: 2. Modeling

Abstract: We find that daytime restratification of the remnant layer is important to modeling both the decay of convective turbulence during the day and convective deepening the following night. Penetrating solar insolation accounted for about 60% of the observed restratification of the remnant layer. Of the other processes supplying the remaining restratification, we believe lateral advection is the most important and sets a limit on the capabilities of one-dimensional mixed-layer models. In the morning, with the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
(1 reference statement)
3
21
0
Order By: Relevance
“…[1986] to a site 800 km west of Point Conception, California, used the much shorter attenuation lengths characteristic of Jerlov Type IA water [Brainerd and Gregg, 1993b]. It also appears that strong variability in surface forcing on length scales of a few kilometers due to squalls contributes significantly to restratification through the relaxation of lateral density variations into stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1986] to a site 800 km west of Point Conception, California, used the much shorter attenuation lengths characteristic of Jerlov Type IA water [Brainerd and Gregg, 1993b]. It also appears that strong variability in surface forcing on length scales of a few kilometers due to squalls contributes significantly to restratification through the relaxation of lateral density variations into stratification.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the effect of rainfall, we applied the PriceWeller-Pinkel mixed layer model (PWP) [Price et al, 1986] to the observations at 0øN in much the same way we earlier applied it to the diurnal cycle at midlatitudes [Brainerd and Gregg, 1993b]. Initializing with a nighttime profile during deep convection, we forced the model for 12 days with the cruiseaveraged daily meteorological cycle (with rainfall set to zero).…”
Section: Mixed and Mixing Layers Restratificationmentioning
confidence: 99%
“…However, TKE dissipation values observed with salt fingers are orders of magnitude below the observed values of the SPURS-I field campaign within DWLs. Brainerd and Gregg (1993b) discuss that because Weller and Price (1988) did not find a minimum wind speed necessary for the development of Langmuir circulation, they may be responsible for some mixing in the SBL. By examining spatial scales less than a kilometer, Farrar et al (2007) have also shown that internal waves can modulate the mixing of the DWL and impact diurnal warming.…”
Section: Past Work and Present State Of Knowledgementioning
confidence: 99%
“…Provided there is adequate depth between the newly formed diurnal thermocline and the seasonal stratification, an initially well-mixed intermediate region is present that is isolated from wind shear. Brainerd and Gregg [1993] referred to this region as the remnant layer and found that, in the ocean, dissipation within this region decayed gradually over a period of 4 h from night time values. When wind speed increases near midday, z MO deepens below z AML .…”
Section: The Diurnal Cycle Of the Actively Mixing Layer And Of The Momentioning
confidence: 99%
“…Depending on the strength of the diurnal stratification, the intensity of night time cooling and wind stress, z AML , may or may not reach the top of the seasonal thermocline. Limnological studies quantifying the diel variability of turbulence and thermal stratification within the upper water column include Imberger [1985], Jonas et al [2003], Anis and Singhal [2006], and Pernica et al [2014], and oceanographic studies include Shay and Gregg [1986], Brainerd and Gregg [1993], and Anis and Moum [1994].…”
Section: The Diurnal Cycle Of the Actively Mixing Layer And Of The Momentioning
confidence: 99%